Distinct properties of the egress‐related osmiophilic bodies in male and female gametocytes of the rodent malaria parasite Plasmodium berghei. (25th November 2014) - Olivieri, Anna; Bertuccini, Lucia; Deligianni, Elena; Franke‐Fayard, Blandine; Currà, Chiara; Siden‐Kiamos, Inga; Hanssen, Eric; Grasso, Felicia; Superti, Fabiana; Pace, Tomasino; Fratini, Federica; Janse, Chris J.; et al.
Summary Gametogenesis is the earliest event after uptake of malaria parasites by the mosquito vector, with a decisive impact on colonization of the mosquito midgut. This process is triggered by a drop in temperature and contact with mosquito molecules. In a few minutes, male and female gametocytes escape from the host erythrocyte by rupturing the parasitophorous vacuole and the erythrocyte membranes. Electron‐dense, oval‐shaped organelles, the osmiophilic bodies (OB), have been implicated in the egress of female gametocytes. By comparative electron microscopy and electron tomography analyses combined with immunolocalization experiments, we here define the morphological features distinctive of male secretory organelles, hereafter named MOB (male osmiophilic bodies). These organelles appear as club‐shaped, electron‐dense vesicles, smaller than female OB. We found that a drop in temperature triggers MOB clustering, independently of exposure to other stimuli. MDV1/PEG3, a protein associated with OB in Plasmodium berghei females, localizes to both non‐clustered and clustered MOB, suggesting that clustering precedes vesicle discharge. A P. berghei mutant lacking the OB‐resident female‐specific protein Pbg377 displays a dramatic reduction in size of the OB, accompanied by a delay in female gamete egress efficiency, while female gamete fertility is not affected. Immunolocalization experiments indicated that MDV1/PEG3 is still recruited to OB‐remnant structures.